Design of data confidential and reliable bee clustering routing protocol in MANET (Vol 2) - RB, Sajyth; G, Sujatha (International Journal of Engineering and Technology, 2018)
Mobile ad hoc network (MANET) requires extraneous energy effectualness and legion intelligence for which a best clustered based approach is pertained called the “Bee-Ad Hoc-C”. In MANET the mechanism of multi-hop routing is imperative but may leads to a challenging issue like lack of data privacy during communication. ECC (Elliptical Curve Cryptography) is integrated with the Bee clustering approach to provide an energy efficient and secure data delivery system. Even though it ensures data confidentiality, data reliability is still disputable such as data dropping attack, Black hole attack (Attacker router drops the data without forwarding to destination). In such cases the technique of overhearing is utilized by the neighbor routers and the packet forwarding statistics are measured based on the ratio between the received and forwarded packets. The presence of attack is detected if the packet forwarding ratio is poor in the network which paves a way to the alternate path identification for a reliable data transmission. The proposed work is an integration of SC-AODV along with ECC in Bee clustering approach with an extra added overhearing technique which n on the whole ensures data confidentiality, data reliability and energy efficiency.
Keywords: Mobile Ad Hoc Networks; Elliptical curve Cryptography; Bee Ad Hoc Clustering; and Overhearing.